Cultural and Environmental Services in Batang Arau River: Heritage and Sustainability - Yuliza, Yenni; Yonariza, Yonariza; Febriamansyah, Rudi; Ridwan, Endrizal (SAFE-Network, 2025)
This study examines the interconnection between cultural ecosystem services, community practices, and environmental degradation in the downstream area of the Batang Arau River, Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews, archival analysis, and field observations. Findings indicate that the river functions not only as an ecological system but also as a cultural and social space, historically tied to traditions such as Selaju Sampan Dayung Palinggam and riverside livelihoods. However, ecological decline—driven by pollution, sedimentation, and weak institutional coordination—has disrupted cultural services, reduced community attachment, and weakened environmental stewardship. The results emphasize that sustainable ecosystem management (SEM) in urban river systems requires more than ecological restoration; it must also include socio-cultural revitalization and participatory governance. Theoretically, this study expands sustainability literature by underscoring the role of cultural ecosystem services and place-based identity. Empirically, it provides grounded evidence that informs inclusive policy strategies, highlighting community-based tourism, heritage conservation, and environmental education as pathways to restore ecological and cultural integrity.